J’ai l’impression que: Lexical Bundles in the Dialogues of Beginner French Textbooks - Vandeweerd, Nathan; Keijzer, Merel (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2018)
Formulaic language is notoriously difficult for second language learners of French to master (Edmonds, 2014; Forsberg, 2010). Yet, no study has examined formulaic language in French textbooks despite the fact that in many contexts, textbooks represent a significant proportion of the input that learners receive. The current study addresses this gap. Using a distributional approach (as used in Biber, Conrad, & Cortes, 2004), four-word lexical bundles were extracted from an oral corpus of French. The average number of lexical bundles in oral corpus utterances was compared to the average number of bundles in a corpus of A1-B1 level textbook dialogues. An independent samples t test showed that the average number of lexical bundles per 100,000 words was significantly higher in texts from the oral corpus than the textbook corpus. The average number of stance and referential lexical bundles was also revealed to be higher in the oral corpus. Implications for textbook design are discussed, such as increasing the amount of formulaic language in A2 level textbooks and incorporating more authentic language into textbooks.